2014
DOI: 10.1002/anie.201404948
|View full text |Cite
|
Sign up to set email alerts
|

Image‐Contrast Technology Based on the Electrochemiluminescence of Porous Silicon and Its Application in Fingerprint Visualization

Abstract: The electrochemiluminescence (ECL) of porous silicon (pSi) has attracted great interest for its potential application in display technology and chemical sensors. In this study, we found that pSi with a different surface chemistry displayed an apparently different dynamic ECL process. An image-contrast technology was established on the basis of the intrinsic mechanism of the ECL dynamic process. As a proof of principle, the visualization of latent fingerprints (LFPs) and in situ detection of TNT in fingerprints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 29 publications
1
53
1
Order By: Relevance
“…This method is particularly useful in visualizing LFPs on metal surfaces, e.g., stainless steel [48], that are often found in felony cases. Recently, Tan et al [49] demonstrated the visualization of oily LFPs and in situ detection of TNT in fingerprints by using an ECL-based image-contrast technology on the surface of porous silicon. Unlike the ECL based on molecular luminescence, this technology does not require a co-reactant.…”
Section: Electrochemical Techniquesmentioning
confidence: 99%
“…This method is particularly useful in visualizing LFPs on metal surfaces, e.g., stainless steel [48], that are often found in felony cases. Recently, Tan et al [49] demonstrated the visualization of oily LFPs and in situ detection of TNT in fingerprints by using an ECL-based image-contrast technology on the surface of porous silicon. Unlike the ECL based on molecular luminescence, this technology does not require a co-reactant.…”
Section: Electrochemical Techniquesmentioning
confidence: 99%
“…Traditional ECL luminophores include metal complexes [36], luminol [37], silicon nanoparticles [38], and quantum dots [39]. Carbon materials, such as graphite-like carbon nitride, carbon nanodots, graphene as well as its composites, have also been studied as ECL emitters [40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new techniques such as electrochemiluminescence and nanotechnology have been applied toward the enhanced development of latent fingermarks [611]. In particular, the use of fluorescent nanoparticles (NPs), such as quantum dots (QDs), for the development of latent fingermarks has attracted significant research interest in forensic science [1218]; this is because of their unique physical and chemical properties such as small particle size, large surface area, good photochemical stability, and high fluorescent intensity.…”
Section: Introductionmentioning
confidence: 99%